Ligand‐Free, Cu‐ and Fe‐Catalyzed Selective Ring‐Opening Arylations of Benzoxazoles with Aryl Iodides. Issue 11 (11th May 2016) - He, Yue; Mao, Jincheng; Rong, Guangwei; Yan, Hong; Zhang, Guoqi
Abstract: Cu‐ or Fe‐based catalyst systems have been reported to selectively catalyze the N, N ‐diarylation or N ‐monoarylation of benzoxazoles ring‐opening with aryl iodides in the absence of additional added ligand in polyethylene glycol under an inert atmosphere. Two types of coupling products (triphenylamines and diphenylamines) have been examined and the reaction routes can be simply controlled by changing the metal salts (Cu or Fe) as catalyst. A range of substrates have been investigated for the diverse reactions, and the corresponding arylation products were achieved in good to high yields. This selective, low‐cost, and environmentally friendly protocol displays great potential for replacing existing methodologies as well as extending the synthetic applications of benzoxazoles. Abstract : Two for One : Cu‐ or Fe‐based catalyst systems have been reported to selectively catalyze the N, N ‐diarylation or N ‐monoarylation, respectively, of benzoxazoles with aryl iodides in the absence of ligand in polyethylene glycol under an inert atmosphere. This selective, low‐cost, and environmentally friendly protocol has great potential in replacing existing methods as well as extending the synthetic applications of benzoxazoles.